Impacts of forestry planting on primary production in upland lakes from north-west Ireland - Stevenson, Mark A.; McGowan, Suzanne; Anderson, N. John; Foy, Robert H.; Leavitt, Peter R.; McElarney, Yvonne R.; Engstrom, Daniel R.; Pla-Rabés, Sergi (Wiley, 2016)
Planted forests are increasing in many upland regions world-wide, but knowledge about their potential effects on algal communities of catchment lakes is relatively unknown. Here the effects of afforestation were investigated using palaeolimnology at six upland lake sites in the north-west of Ireland subject to different extents of forest plantation cover (4-64% of catchment area). 210Pb dated sediment cores were analysed for carotenoid pigments from algae, stable isotopes of bulk carbon (δ13C) and nitrogen (δ15N), and C/N ratios. In lakes with >50% of their catchment area covered by plantations, there were two- to six-fold increases in pigments from cryptophytes (alloxanthin) and significant but lower increases (39-116%) in those from colonial cyanobacteria (canthaxanthin), but no response from biomarkers of total algal abundance (β-carotene). In contrast, lakes in catchments with <20% afforestation exhibited no consistent response to forestry practices, although all lakes exhibited fluctuations in pigments and geochemical variables due to peat cutting and upland grazing prior to forest plantation. Taken together, patterns suggest that increases in cyanobacteria and cryptophyte abundance reflect a combination of mineral and nutrient enrichment associated with forest fertilisation and organic matter influx which may have facilitated growth of mixotrophic taxa. This study demonstrates that planted forests can alter the abundance and community structure of algae in upland humic lakes of Ireland and Northern Ireland, despite long histories of prior catchment disturbance.